UK-18892, a New Aminoglycoside: An In Vitro Study - Wise, R. (1978)
UK-18892 is a new aminoglycoside antibiotic, a derivative of kanamycin A structurally related to amikacin. It was found to be active against a wide range of pathogenic bacteria, including many gentamicin-resistant strains. The spectrum and degree of activity of UK-18892 were similar to those of amikacin, and differences were relatively minor. UK-18892 was about twice as active as amikacin against gentamicin-susceptible strains of Pseudomonas aeruginosa. Both amikacin and UK-18892 were equally active against gentamicin-resistant strains of P. aeruginosa. There were no appreciable differences in the activity of UK-18892 and amikacin against Enterobacteriaceae and Staphylococcus aureus. Cross-resistance between these two antimicrobials was also apparent.